Medical imaging literature in MyCite - Kamarudin, Nurul Husna; A. Rahman, Nor Azlina; Zainuddin, Zainul Ibrahim (UPM Press, 2019)
The presence of imaging technologies in Malaysia needs to be supported by homegrown research to optimize and tailor their usage for local benefits. Research done elsewhere may not be applicable to local situations. This study investigates the contribution of researches by Malaysian academicians and service providers to the field of medical imaging, as evident in the Malaysian Citation index (MyCite) database. Bibliometric and thematic analyses were performed on publications featured in the database from 2006 to 2016. The bibliometric analysis provided information on the affiliation of the authors, their professional backgrounds, types of studies, and the journals involved while the thematic analysis identified the themes and sub-themes of identified articles. The study found that Malaysians contributed 54.1% of the publications, followed by non-Malaysians (41.8%) and collaboration authors (4.1%). Researchers were mostly from university-based and hospital university-based institutions. The thematic analysis presented that 42.9% of articles were classified under clinical themes. The results also suggested that the current trends of research in medical imaging are focused on topics involving clinical and modality, and only a few patient-centered researches. This is an indication that more researches that are relevant to local practices and needs are required as this will strengthen the medical imaging practice in the country.